PERSONALITY TRAITS, RESILIENCE AND PERCEIVED SOCIAL SUPPORT PREDICTING QUALITY OF LIFE AMONG BEREAVED YOUNG ADULTS - Oyeniyi, Opeoluwa; Ehondor, Esohe; James, Olubunmi; Uye, Emmanuel (Jurnal Saintifik (Multi Science Journal), 2025)
Quality of life has become a broad-based construct used to evaluate various aspects of human well-being including the period of bereavement. Studies linking quality of life with the period of individuals’ bereavement are lacking. Therefore, this study investigates personality traits, resilience and perceived social support as predictors of quality of life among bereaved young adults in Ibadan. Ex-post facto design utilizing cross-sectional survey was used while purposive sampling technique was used to select the study location. Data were collected from 187 bereaved young adults using validated questionnaires and analyzed using multiple regression and independent samples t-test. Two hypotheses were tested and accepted at p <.05 level of significance. The result demonstrated that personality traits, resilience and perceived social support jointly predicted quality of life among study participants In addition extraversion agreeableness and perceived social support independently predicted quality of life among study participants. Furthermore, there was a gender difference in quality of life among study participants. The study concludes that interactions of personality traits, resilience and perceived social support are good predictors of quality of life among study participants. The study recommended design and implementation of psychological counseling, resilience training, and personality profiling to help bereaved individuals to improve quality of life.